Coupling Model of Regional Economic System Design Based on Big Data Technology - Jin, Huan (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
The regional economic system lacked accurate calculation of data and reasonable allocation of internal resource requirements in the market operation. For this reason, the design of the regional economic system coupling model based on big data technology was carried out. On the basis of the analysis of regional economic coupling innovation development, the hardware design of regional economic system focused on the standard processing and assignment of coupled raw data to determine the index weight; In the software design, the coupling degree model of the interaction force between several systems was established by comparing the coupling definition in physics and the size of the capacity coupling coefficient. The research proves that from the perspective of time, the coupling fitness of regional economic systems was increasing year by year. However, the overall goal of coupling was small; from a spatial point of view, the coupling fitness had a clear spatial inconsistency distribution.